Putting Politics First: The Impact of Politics on American Religious and Secular Orientations. Issue 3 (6th June 2018) - Campbell, David E.; Layman, Geoffrey C.; Green, John C.; Sumaktoyo, Nathanael G.
Abstract: Nearly all research on the political impact of Americans' religious and secular orientations assumes that such orientations are exogenous to politics. Using multiwave panel and experimental data, we find that religious and secular orientations are endogenous to political orientations. In other words, religion and secularism are a consequence as well as a cause of politics. In showing this, we make three major contributions. First, we conceptualize and measure secular orientations in a new way—not just as the absence of religion, but also as an affirmative secular identity and positive commitment to secular principles. Second, our panel and experimental data allow for the most definitive test to date of whether political orientations exert a causal effect on religious and secular orientations. Third, we isolate the conditions under which politics affects religious–secular perspectives, thus identifying the mechanism that underlies political orientations.